6y-12=9(y+2)

Simple and best practice solution for 6y-12=9(y+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-12=9(y+2) equation:



6y-12=9(y+2)
We move all terms to the left:
6y-12-(9(y+2))=0
We calculate terms in parentheses: -(9(y+2)), so:
9(y+2)
We multiply parentheses
9y+18
Back to the equation:
-(9y+18)
We get rid of parentheses
6y-9y-18-12=0
We add all the numbers together, and all the variables
-3y-30=0
We move all terms containing y to the left, all other terms to the right
-3y=30
y=30/-3
y=-10

See similar equations:

| 5n+5=40-2n | | 1.71x=100 | | d2−12d=−36 | | 6h-5-h2=4 | | 7=(x-42)/12 | | 5n+5=40+ | | y+11/10=4 | | 2(x+6)=1(x-10) | | 3×(4-3x)=2×(9-6x) | | 90+x+4+x-10=180 | | x*0.05=630000 | | 8x-12=-4x+72 | | 3x+-2+8=2x | | x-0.05=630000 | | 7=x-42/12 | | 7x+12=75* | | x+-0.05=630000 | | 28+0.09x=0.13x | | 8x-12=-4x+108 | | 2/5x-12=4/5 | | -12r+11=-r2 | | y/4+1=12 | | 4z+4=5z-4 | | 7x+9=4x-30 | | -4+z/5=5 | | 9^3x+1=27^x | | 100m-48,250=50,250-150m | | 8(y-2)=5y-7 | | 4–(3x–5)=2x–26 | | 2x+13+x=1-9x+22 | | 3×(+4-3x)=2×(+9-6x) | | 3x-2=8x-13 |

Equations solver categories